Descriptive Analysis of the Effectiveness of Learning Physics for Biology at Mataram University - Cahaya Rizkika Imanda; Maratus Soleha; Mira Suhada; Wahyu Lina Ramadani; Baiq Nabila Nasywa; Halia Safitri; Kormil Saputra; Fatima Naimi (Education Specialist, 2025)
This study aimed to evaluate the effectiveness of physics learning for biology students at the University of Mataram, focusing on understanding, application of concepts, and the relevance of materials to biological studies. The research employed a quantitative approach using a Likert-scale questionnaire distributed to 40 Biology program students. Data were analyzed using descriptive statistics to identify trends in students' perceptions of the effectiveness and satisfaction with physics learning. The results revealed that most students considered physics learning moderately effective, particularly through practical sessions, although the prevalence of neutral responses indicated a need to improve material relevance and teaching methods. Practical sessions significantly supported concept comprehension, yet challenges remained in connecting physics materials to practical applications in biology. Student satisfaction with teaching methods was relatively positive, but improvements in material delivery and laboratory facilities were also highlighted as critical areas. This study recommends strengthening the integration of physics with biological contexts, optimizing practical sessions, and developing teaching methods utilizing interactive technology and case studies to enhance student engagement.